Book & Film Reviews - Bawono, Haryo Tejo (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2022)
Book & Film Reviews is a column in "MELINTAS" containing reviews of books and films published recently that bring different interpretation and inspiration to the fields of philosophy and religion.